Association Between Inferior Turbinate Hypertrophy and Extraesophageal Reflux - Zeleník, Karol; Javorská, Zuzana; Taimrová, Renata; Vrtková, Adéla; Hránková, Viktória; Tedla, Miroslav; Lukácová, Kristína; Lubojacký, Jakub; Formánek, Martin; Komínek, Pavel (JAMA otolaryngology-- head & neck surgery, 2022)
IMPORTANCE: To the authors' knowledge, no prior studies have examined the association between inferior turbinate hypertrophy (ITH) and extraesophageal reflux (EER). If EER were a cause or cofactor of ITH, antireflux treatment can be considered prior to surgical intervention. OBJECTIVE: To evaluate EER presence and severity in patients with different degrees of ITH. DESIGN, SETTING, AND PARTICIPANTS: Prospective multicentric cohort study conducted at 3 referral centers treating patients with EER and certified for 24-hour monitoring of oropharyngeal pH. The monitoring was performed between October 2020 and October 2021. A total of 94 adult patients with EER symptoms were recruited, 90 of whom were analyzed. INTERVENTIONS: Nasal endoscopy was performed to determine the degree of ITH, according to the Camacho classification. Presence and severity of EER were examined using 24-hour monitoring of oropharyngeal pH. MAIN OUTCOMES AND MEASURES: Primary outcomes were presence of EER according to RYAN Score, total percentage of time below pH 5.5, and total numbers of EER events below pH 5.5. RESULTS: Of the 90 analyzed patients (median [IQR] age, 46 [33-58] years; 36 [40%] male patients), 41 had a maximum of second-degree ITH (group 1), and 49 patients had at least third-degree ITH (group 2), according to the Camacho classification. On the basis of the RYAN Score, EER was diagnosed more often in group 2 (69.4%) than in group 1 (34.1%; difference, 35.3% [95% CI, 13.5%-56.9%]). Moreover, compared with group 1, group 2 exhibited higher median total percentage of time below pH 5.5 (median [IQR], group 1: 2.1% [0.0%-9.4%], group 2: 11.2% [1.5%-15.8%]; difference, 9.1% [95% CI, 4.1%-11.8%]) and higher median total number of EER events (median [IQR], group 1: 6 [1-14] events, group 2: 14 [4-26] events; difference, 8 [95% CI, 2-15] events). Patients with proven EER demonstrated no difference in the degree of ITH between the right and left nasal cavity (Cohen g, -0.17 [95% CI, -0.50 to 0.30]), or between the anterior and posterior parts of the nasal cavity (Cohen g, -0.21 [95% CI, -0.50 to 0.17]). CONCLUSIONS AND RELEVANCE: In this cohort study, patients with a higher degree of ITH had more severe EER. A possible association between severe ITH and EER was demonstrated.
Keywords: nosní skořepy; Male; kohortové studie; Cohort Studies; Paranasal Sinus Diseases; Adult; Prospective Studies; dospělí; mužské pohlaví; nemoci vedlejších nosních dutin; hypertrofie; gastroezofageální reflux; lidé; ženské pohlaví; Humans; Hypertrophy; Female; lidé středního věku; Gastroesophageal Reflux; Turbinates; Middle Aged; prospektivní studie